2003
DOI: 10.1289/ehp.6171
|View full text |Cite
|
Sign up to set email alerts
|

Short-term exposure of Chinook salmon (Oncoryhnchus tshawytscha) to o,p-DDE or DMSO during early life-history stages causes long-term humoral immunosuppression.

Abstract: We evaluated the effect of short-term exposures to a xenobiotic chemical during early life-history stages on the long-term immune competence of chinook salmon (Oncoryhnchus tshawytscha). Immersion of chinook salmon eggs in a nominal concentration of o,p´-dichlorodiphenyldichloroethylene (o,p´-DDE; 10 ppm) for 1 hr at fertilization followed by immersion in the same dose for 2 hr at hatch resulted in a significant reduction in the ability of splenic leukocytes from fish 1 year after treatment to undergo blastoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 78 publications
(80 reference statements)
0
38
0
Order By: Relevance
“…Metcalfe et al (2000) suggested that continuous exposure to endocrine active compounds such as o,p 0 -DDT must begin in ovo and continue throughout early development to affect reproductive endpoints in fish. (Milston et al, 2003). Visual and vibratory stimuli responses and routine swimming activity were impaired in Atlantic croaker larvae exposed to o,p 0 -DDT, which may decrease survival by increasing predation, decreasing feeding rates, or both (Faulk et al, 1999).…”
Section: Childersburg Eureka Lavaca Mcintosh Bucksmentioning
confidence: 99%
See 1 more Smart Citation
“…Metcalfe et al (2000) suggested that continuous exposure to endocrine active compounds such as o,p 0 -DDT must begin in ovo and continue throughout early development to affect reproductive endpoints in fish. (Milston et al, 2003). Visual and vibratory stimuli responses and routine swimming activity were impaired in Atlantic croaker larvae exposed to o,p 0 -DDT, which may decrease survival by increasing predation, decreasing feeding rates, or both (Faulk et al, 1999).…”
Section: Childersburg Eureka Lavaca Mcintosh Bucksmentioning
confidence: 99%
“…Dietary exposure to technical DDT has reduced survival in fish at multiple life stages (see review by Jarvinen and Ankley, 1999), and protective thresholds for whole-body total DDT concentrations have been recommended for early life stage, juvenile, and adult fish (Beckvar et al, 2005). In addition, exposure to p,p 0 -DDE, o,p 0 -DDT, and o,p 0 -DDE can affect behavior and disrupt the endocrine and immune systems in fish (Donohoe and Curtis, 1996;Ungerer and Thomas, 1996;Faulk et al, 1999;Milston et al, 2003;Papoulias et al, 2003;GarciaReyero et al, 2006;Barber et al, 2007). Exposure to p,p 0 -DDE has been associated with reduced reproductive success of bird populations; bald eagle (Haliaeetus leucocephalus) and osprey (Pandion haliaetus) are especially susceptible to eggshell thinning after exposure (Anderson and Hickey, 1972;Wiemeyer et al, 1984Wiemeyer et al, , 1988.…”
mentioning
confidence: 99%
“…It is not clear whether immunosuppression in juvenile chinook leads to continued adverse effects at later ages or if open ocean chemical exposures result in sufficient tissue concentrations to trigger or maintain immune suppression. A recent laboratory study by Milston et al (2003) observed humoral immunosuppression 1 year after a two-step exposure (a 1-h exposure followed a month later by a 2-h exposure) of chinook embryos to sublethal concentrations of dichlorodiphenyldichloroethylene (DDE).…”
Section: Immune Toxicity Scenariosmentioning
confidence: 99%
“…These OCPs may have toxic effects on several non-target aquatic organisms, and even on aquatic ecosystems. Previous studies have reported that dietary exposure to OCPs led to reduced survival rates in fish at multiple life stages, including early life, the juvenile and adult stages (Barber et al 2007;Beckvar et al 2005;Milston et al 2003;Papoulias et al 2003). Exposure to DDTs may affect behavior and disrupt the endocrine and immune systems in fish (Barber et al 2007;Milston et al 2003;Papoulias et al 2003).…”
Section: Introductionmentioning
confidence: 99%